Pengembangan Sistem Informasi Manajemen Inventaris Obat yang Berbasis Metode Economic Order Quantity (EOQ) dan Diimplementasikan dengan PHP-MySQL - Rasyida Shabihah Zukro Aini; Elsa Sari Hayunah Nurdiniyah; Muhammad Adib Syamlan; Mahesa Sangga Bhuwana (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Manual drug record-keeping in private pharmacies often results in inefficiency, errors, and data loss, disrupting stock and operational management. To overcome these issues, a web-based drug management system was developed using XAMPP, MySQL, and PHP. The system provides role-based access for managers, admins, and pharmacists, and integrates seven key functions: user registration, login/logout, drug data entry, stock monitoring, EOQ-based stock classification, drug distribution to branch pharmacies, and deletion of invalid stock data. The system enables real-time stock monitoring, reduces error risks, and improves efficiency in managing central and branch pharmacy operations. Its contribution lies in integrating EOQ-based stock classification with inter-branch coordination in a single web platform, strengthening the application of information technology in pharmaceutical management and offering a foundation for future development of pharmacy information systems.